Desarrollo e implementación de business intelligence para el soporte a la toma de decisiones de la empresa distribuidora CSM E.I.R.L. 2022. - Passapera Monsalve, David D. Junior (2025)
This research addresses the question: How does the development of a business intelligence (BI) solution improve decision-making in the company Distribuidora CSM E.I.R.L.? The main objective was to determine how the implementation of a BI solution impacts decision-making, while the specific objectives focused on reducing the time required to generate reports, improving decision-making effectiveness, and increasing information availability. The research was conducted with a mixed approach and applied type, also known as practical or empirical research. The design was pre-experimental with a single group and pre- and post-test measurements, allowing the evaluation of the effect of the BI solution before and after its implementation. The results showed significant improvements in all analyzed indicators: the perception of the average time to obtain reports improved from 10.94 to 20.81 points, information availability increased from 7.97 to 23.13 points, and decision-making effectiveness rose from 13.00 to 22.63 points. Statistical analysis with the Wilcoxon test yielded a p-value of 0.000 for all hypotheses, confirming the significance of these improvements. It is concluded that the implementation of the BI solution optimized decision-making in Distribuidora CSM E.I.R.L., reducing times, increasing information accessibility, and enhancing decision quality, highlighting the positive impact of using BI on organizational efficiency.